Synchronous rise and fall of bark beetle and parasitoid populations in windthrow areas. (11th July 2013) - Wermelinger, B.; Obrist, M. K.; Baur, H.; Jakoby, O.; Duelli, P.
Abstract: Windthrows in spruce forests provide a prime substrate for the population build‐up of bark beetles. Until now, no information has been available on the population development of associated parasitoids. The development of bark beetle and parasitoid populations was monitored on cleared and uncleared windthrow areas for 4 years, corresponding to the second to fifth growing seasons after the storm. The population level of both groups quickly increased synchronously from the second to the third season, and gradually declined thereafter until the fifth growing season. The parasitoids showed no time lag. At the species level, the same pattern was found for the pest Ips typographus (L.) and its specific parasitoid Dinotiscus eupterus (Walk.). During the 4 years under study, a succession of different bark beetle and parasitoid species was found. Bark beetles and parasitoids were more abundant on uncleared windthrow areas than on cleared areas, whereas predatory beetles generally preferred the adjacent forest. Once the deteriorated phloem quality precludes further bark beetle development, no more bark beetle‐relevant parasitoids are produced in windthrows.